Fry bread : a Native American family story - Maillard, Kevin Noble (Roaring Brook Press, 2019)
Using illustrations that show the diversity in Native America and spare poetic text that emphasizes fry bread in terms of provenance, this volume tells the story of a post-colonial food that is a shared tradition for Native American families all across the North American continent. Includes a recipe and an extensive author note that delves into the social ways, foodways, and politics of America's 573 recognized tribes.